2003
DOI: 10.1002/rcm.1147
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometry in studies of aluminium(III)–ligand solution equilibria

Abstract: Electrospray ionization mass spectrometry (ESI-MS) has been applied to the study of solution equilibria between Al(III) and the two ligands 4-hydroxy-3-pyridinecarboxylic acid (4H3P) and 3-hydroxy-4-pyridinecarboxylic acid (3H4P). The results compare well with the speciation data obtained from potentiometric, UV-visible spectroscopy, and NMR measurements. This agreement suggests the applicability of ES-MS to the study of more complicated aluminium-ligand systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 49 publications
2
25
0
1
Order By: Relevance
“…However, metal-complexes usually loose their inner-sphere water during the ionization process. [34,35] Remarkable exceptions could be the Al 2 HL 2 ðH 2 OÞ þ 2 and Al 2 HL 2 (H 2 O) + complexes found in this study, although the second one could also be the partially de-solvated fragment of the first. Moreover, the Al 2 HL 2 ðH 2 OÞ þ 2 formula could also be derived in an other way, since a dihydroxo bridged dimer has the formula of Al 2 H 3 L 2 ðOHÞ 2 ðH 2 OÞ þ 2 (see also DFT calculations below).…”
Section: Electro-spray Ionization Mass Spectrometrymentioning
confidence: 49%
“…However, metal-complexes usually loose their inner-sphere water during the ionization process. [34,35] Remarkable exceptions could be the Al 2 HL 2 ðH 2 OÞ þ 2 and Al 2 HL 2 (H 2 O) + complexes found in this study, although the second one could also be the partially de-solvated fragment of the first. Moreover, the Al 2 HL 2 ðH 2 OÞ þ 2 formula could also be derived in an other way, since a dihydroxo bridged dimer has the formula of Al 2 H 3 L 2 ðOHÞ 2 ðH 2 OÞ þ 2 (see also DFT calculations below).…”
Section: Electro-spray Ionization Mass Spectrometrymentioning
confidence: 49%
“…In their work, Matsumoto et al detected a ternary copper(II)-2-(5-bromo-2-pyridilazo)-5-diethylaminophenol-acetate species, Cu 2 L 2 AcO, but they did not detect the corresponding nickel(II) species. Another approach (Matsumoto et al, 1999;Di Marco et al, 2003) implies the analysis of the peak intensities of a species at decreasing metal concentrations but at the same pH and metal-to-ligand ratio: in the presence of gas-phase reactions, peak intensities are expected to vary with metal concentration and with respect to equilibrium data. Unfortunately, this latter approach requires the previous knowledge of the equilibrium composition of the solution under examination.…”
Section: Gas-phase Reactionsmentioning
confidence: 99%
“…The authors reported some hypotheses to explain these quantitative differences; apart from gas-phase reactions and from pH drifts during the electrospray process, the differences would stem from the low response factor of the neutral complexes at neutral and basic pH values, where a low concentration of proton is available to charge these species thus allowing their detection. Di Marco et al (Bertani et al, 1999;Di Marco et al, 2003) studied the complexes formed between Al 3þ and some hydroxypyridinecarboxylic acids in a 3:1 water-methanol system at several pH values and metal-ligand ratios, and they compared ESI-MS results with previous reported potentiometric data. The qualitative speciation (number and stoichiometries of the complexes) agreed with the results obtained from potentiometric titrations, while the quantitative agreement was poor in some cases and fair in others.…”
Section: Comparison Between Quantitative Esi-ms and Other Techniques mentioning
confidence: 99%
“…Among the several phenomena which in MS analysis may perturb the equilibrium state, 1 only gas-phase reactions and differences in ion response factors should be significant for Al(III) complexes. 9 The similarity of gas-phase reactions and of ion response factors in SACI and in ESI are therefore suggested. SACI spectra of adequate quality could not be obtained for solutions containing Al(III) and either 2, 3, and 4 (corresponding spectra are therefore not reported).…”
mentioning
confidence: 99%